Hydraulic Characteristics and Numerical Simulation of the Entrance Section of Ladder-Shaped Spillway - X. B. Gu; Q. H. Wu; Y. Wang; H. X. Zhao (Geofluids)
The ladder-shaped spillway in a certain reservoir junction is set as the engineering background in the paper. The hydraulic similarly model experiment and three-dimensional numerical simulation of hydraulic characteristics of water flow are performed. The outflow capacity, flow state analysis, velocity distribution, water surface line, pressure, and the energy dissipation rate are analyzed, and experimental results are compared with the numerical results. The conclusions demonstrate that the numerical results of the flow characteristics are very proximate to actual experimental results, the changeable law is the same, and their energy dissipation rate is basically consistent; it shows the feasibility of three-dimensional numerical simulation; the conclusions can provide the basis for the optimization about the flow state of the ladder-shaped spillway in the future.